MENGEMBANGKAN KEMAMPUAN MOTORIK HALUS DAN TANGGUNG JAWAB ANAK MELALUI PENERAPAN MODEL PROJECT BASED LEARNING DAN DISCOVERY LEARNING DENGAN MEDIA AMPAS KELAPA PADA ANAK KELOMPOK A3 TK NEGERI PEMBINA BANJARMASIN TENGAH - Rina Susanti; Putri Nur Ellyza; Muhammad Wahyu Erfani; Celia Cinantya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted based on preliminary classroom observations that revealed low levels of learning activities, fine motor skills, and responsibility among Group A3 children at TK Negeri Pembina Banjarmasin Tengah. The identified problems included children's limited participation in learning activities, inadequate hand-eye coordination during task performance, and an underdeveloped sense of responsibility in using and organizing learning tools and materials. This study aimed to improve children's learning activities, fine motor skills, and responsibility through the implementation of the Project Based Learning (PjBL) and Discovery Learning models using coconut pulp as instructional media. This study employed a collaborative Classroom Action Research (CAR) design conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The participants were 17 children from Group A3 at TK Negeri Pembina Banjarmasin Tengah. Data were collected through observation, documentation, and assessment of children's work and analyzed using descriptive qualitative and quantitative methods. The findings showed improvements in all observed aspects and indicators. Children's learning activities increased from 70.59% in Cycle I to 88.23% in Cycle II. Fine motor skills improved from 76.47% (Developing as Expected) to 88.23% (Very Well Developed), while children's responsibility increased from 76.47% to 94.11% (Very Well Developed). Teacher performance also improved from 75.00% to 93.75%. Therefore, the implementation of the Project Based Learning (PjBL) and Discovery Learning models supported by coconut pulp as instructional media was effective in improving the learning activities, fine motor skills, and responsibility of Group A children at TK Negeri Pembina Banjarmasin Tengah.